Bacterial killing by complement requires membrane attack complex formation via surface‐bound C5 convertases. (14th January 2019) - Heesterbeek, Dani AC; Bardoel, Bart W; Parsons, Edward S; Bennett, Isabel; Ruyken, Maartje; Doorduijn, Dennis J; Gorham, Ronald D; Berends, Evelien TM; Pyne, Alice LB; Hoogenboom, Bart W; Rooijakkers, Suzan HM
Abstract: The immune system kills bacteria by the formation of lytic membrane attack complexes (MACs), triggered when complement enzymes cleave C5. At present, it is not understood how the MAC perturbs the composite cell envelope of Gram‐negative bacteria. Here, we show that the role of C5 convertase enzymes in MAC assembly extends beyond the cleavage of C5 into the MAC precursor C5b. Although purified MAC complexes generated from preassembled C5b6 perforate artificial lipid membranes and mammalian cells, these components lack bactericidal activity. In order to permeabilize both the bacterial outer and inner membrane and thus kill a bacterium, MACs need to be assembled locally by the C5 convertase enzymes. Our data indicate that C5b6 rapidly loses the capacity to form bactericidal pores; therefore, bacterial killing requires both in situ conversion of C5 and immediate insertion of C5b67 into the membrane. Using flow cytometry and atomic force microscopy, we show that local assembly of C5b6 at the bacterial surface is required for the efficient insertion of MAC pores into bacterial membranes. These studies provide basic molecular insights into MAC assembly and bacterial killing by the immune system. Synopsis: The complement is an essential part of the immune system that kills target cells via lytic membrane attack complex (MAC) pores. Complement C5 convertases regulate local assembly of MAC pores and their insertion into bacterial membranes to trigger bacterial killing. Purified MAC components generated from preassembled C5b6 perforate artificial lipid membranes but lack bactericidal activity. Local assembly of C5b6 by a C5 convertase is essential to form bactericidal MAC pores that damage both bacterial membranes. Local assembly of C5b6 at the bacterial surface is required for the efficient insertion of MAC pores into bacterial membranes. Abstract : Complement C5 convertases regulate local assembly of the lytic membrane attack complex pores and their insertion into bacterial membranes to trigger bacterial killing.